A smoothed particle hydrodynamics (SPH) model for simulating surface erosion by impacts of foreign particles. (March 2016) - Dong, X.W.; Liu, G.R.; Li, Zengliang; Zeng, W.
Abstract: This paper presents a smoothed particle hydrodynamics modeling procedure to simulate surface erosion by impacts. The present SPH is improved based on the standard SPH formulation, by developing SPH formulations for the constitutive relations to describe plastic behavior and ductile fracture process. The improved SPH method is first applied to simulate impacts of particles on ductile targets. Two modified schemes in terms of density correction and kernel gradient correction are adopted to improve the accuracy of the SPH approximation. The present SPH model is applied to simulate the erosion process by angular particles. The results are compared with available experimental data, and good agreements have been achieved in terms of the crater profile and particle kinematic results. Highlights: A SPH model for simulating surface erosion by impacts of foreign particles is proposed. Johnson–Cook constitutive models are incorporated to capture the material behavior. Interaction between particle and targets is considered through a particle contact algorithm. The improved algorithm improves the accuracy of SPH approximation. Numerical oscillations are suppressed by using corrective terms.